A randomized controlled study of exposure therapy as aftercare for alcohol use disorder: study protocol. Issue 1 (December 2016) - Mellentin, Angelina; Nielsen, Bent; Nielsen, Anette; Yu, Fei; Stenager, Elsebeth
Abstract Background It is well documented that individuals with Alcohol Use Disorder (AUD) respond well during evidence-based psychological treatment, but also that a large proportion relapses when discharged from treatment and confronted with alcohol in real life. Cue Exposure Treatment (CET) focuses on exposing individuals to alcohol cues in order to reduce cravings as well as the likelihood of relapse. The aims of the study are: 1) to investigate whether CET aftercare delivered via a smartphone or in group sessions increases the effect of Cognitive Behavioural Treatment in groups of alcohol dependent individuals; 2) to investigate whether CET as a smartphone application is as or more effective than CET group therapy, and 3) to investigate whether CET as a smartphone application is more cost-effective than CET group aftercare and Aftercare as Usual. Design and methods The study will be implemented as an investigator-blinded randomized controlled trial. A total of 300 consecutively enrolled alcohol use disorder individuals recruited from an alcohol outpatient clinic will be randomized into one of the three following aftercare groups after concluding primary treatment: (1) CET as a smartphone application; (2) CET as group therapy, and (3) Aftercare as Usual. It is hypothesized that the two experimental groups will achieve better treatment outcomes compared to the control group (3). Discussion Individuals in the CET groups are given the opportunity to practise coping strategies during exposure to alcohol stimuli before being unavoidably confronted with alcohol and associated stimuli in real life. Thus, CET may help prevent patients from relapsing after concluding treatment, and in the long term. Moreover, the CET application has the potential to improve AUD treatment and continuing care by offering psychological treatment whenever and wherever the patient finds it convenient. Trial registration ClinicalTrials.gov ID:NCT02298751 Registration date: 6 November 2014